2021
DOI: 10.3390/su13147877
|View full text |Cite
|
Sign up to set email alerts
|

How Green Trust, Consumer Brand Engagement and Green Word-of-Mouth Mediate Purchasing Intentions

Abstract: An increasing interest in environmental problems around the world has significantly expanded the demand for green goods, transforming green marketing into an effective tool for businesses to achieve competitive advantage. Yet, as more firms become aware of this strategic advantage, greenwashing activities can also flourish, and customers grow more cautious about green efforts by firms. The present research examines how greenwashing expectations of customers affect their green buying decisions by studying how g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 47 publications
2
31
1
3
Order By: Relevance
“…Further, this finding agreed with the finding of Sultana et al’s study [ 91 ] which demonstrated that GT has a significant positive effect on customers’ intention to stay at green hotels in Bangladesh. Another study conducted by Guerreiro and Pacheco [ 74 ] concluded that GT is significantly correlated with GWoM and GPI. In their study, they argued that consumers are less likely to purchase or spread positive GWoM about a brand if they do not trust its green claims and/or actions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, this finding agreed with the finding of Sultana et al’s study [ 91 ] which demonstrated that GT has a significant positive effect on customers’ intention to stay at green hotels in Bangladesh. Another study conducted by Guerreiro and Pacheco [ 74 ] concluded that GT is significantly correlated with GWoM and GPI. In their study, they argued that consumers are less likely to purchase or spread positive GWoM about a brand if they do not trust its green claims and/or actions.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies that have been built based on attitude-behavior relationships revealed that GT in the product/brand can subsequently enhance CGBIs such as GPI, GPI, GWoM intentions, premium purchase intentions, and loyalty behavioral intentions [ 36 , 37 , 72 , 73 , 74 ]. Research on green marketing has revealed the significance of GT in predicting GPIs [ 34 , 73 ].…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Therefore, we hypothesize that green practices such as GT and GS will increase visitor numbers. The argument is supported by Guerreiro and Pacheco (2021) that GT significantly leads to consumers purchase intention. Moreover, customers trust boosts their confidence to purchase hotel services or products that improve customer loyalty (Mart ınez, 2015).…”
Section: Green Trust and Green Satisfaction As A Mediatormentioning
confidence: 86%
“…In response to the traditional approach of the role of consumers in the agri-food systems, several concepts and initiatives have been developed considering a more active role for both individual and collective consumers/citizens in the agri-food value chain. For instance, sustainable consumption has emerged in marketing scholarship as a pressing matter [67,69], followed by other initiatives, such as ethical consumption [70], responsible consumer behavior [71], reflexive consumption [72], green procurement/consumption [73] and green certification [74]. However, these initiatives have also narrowed the focus only on the consumption part of the agri-food value chain and the proposed solutions have focused on merely consumers rather than a systemic alternative that encompasses a broader context involving other stages of the value or supply chain.…”
Section: Inputs Farming Processing/ Distribution Retailers Consumersmentioning
confidence: 99%